Thematic Review on Regional Financial Integration and Stability in Asean: From Financial Crises to Digitalisation Era - Wan Nurhanan Wan Suhaimi; Nor Haziah Hashim; Fuadah Johari; Norfhadzilahwati Rahim (Fakulti Ekonomi dan Muamalat, 2025)
International Islamic Economic System Conference (I-iECONS 2025) "Digitalization, Innovation and Sustainable Development Through Islamic Economics"/ editors: Amalina Mursidi & Nur I'ffah Muhammad Nasir Organized by the Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM) Conference Dates: 26-31 August 2025